The Role of Religiosity In Mediating The Effect of Job Satisfaction On Organizational Citizenship Behavior (OCB) - Ardiansyah Ardiansyah; Rizkha Maulana; Rita Andhini (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study investigates how religiosity influences job satisfaction in relation to organizational citizenship behavior (OCB). A quantitative method was employed, involving one hundred permanent employees from various organizations. Data were collected using a five-point Likert scale questionnaire. Structural Equation Modeling (SEM-PLS) was used for analysis. The results indicate that religiosity significantly affects job satisfaction, job satisfaction significantly affects OCB, and religiosity partially mediates the relationship between job satisfaction and OCB. This study affirms that religiosity plays an important role in fostering positive employee behavior in Indonesia.